2018
DOI: 10.1287/msom.2017.0685
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Visibility and Social Responsibility: Investigating Consumers’ Behaviors and Motives

Abstract: Consumers increasingly want to know more about where and how the products they purchase are being made. To create transparency requires a company to both gain visibility into its supply chain and disclose information to consumers. In this paper, we focus on the dimension of visibility and investigate when companies can benefit from greater supply chain visibility. To do so, we design an incentivized human–subject experiment to study two key questions: (i) How does supply chain visibility impact consumers’ valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 74 publications
2
115
0
1
Order By: Relevance
“…Another stream of work explores the impact of supply chain visibility using behavioral methods. For instance, Kraft, Valdés, and Zheng () and Pigors and Rockenbach () use laboratory experiments to show that consumers react positively when firms increase visibility. However, there is limited empirical evidence on the benefits of supply chain visibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another stream of work explores the impact of supply chain visibility using behavioral methods. For instance, Kraft, Valdés, and Zheng () and Pigors and Rockenbach () use laboratory experiments to show that consumers react positively when firms increase visibility. However, there is limited empirical evidence on the benefits of supply chain visibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cho et al (2018) focused on a multinational manufacturer's strategies to combat the use of child labor by the supplier in a developing nation; they showed that with disclosure of the manufacturer's inspection effort, combining the internal inspections with medium wholesale prices can be an effective strategy to deter the use of child labor, but they also noted that information disclosure may backfire, especially when the manufacturer is incentivized to disclose low efforts. Kraft et al (2018) studied the impact of a firm's supply chain visibility, that is, "the extent to which a company has information about the social responsibility practice in its supply chain," and information disclosure decisions on customers' valuation of the firm, through a set of incentivized laboratory experiments. Kraft et al (2013) considered the NGOs' role in providing the customers with information about the use of potential hazardous substances in the supply chains, which will influence a firm's market share in a competitive business environment.…”
Section: Related Literaturementioning
confidence: 99%
“…Although related, our study has new features that are distinct from the above-mentioned studies of supply chain transparency. First, we focus on the buyer's decision to reveal her relationship with the supplier; this is in contrast to previous studies, which focused on disclosure of information regarding what the buyer knows about the supplier's social and environmental impact (e.g., Kalkanci et al 2016, Kraft et al 2013, the buyer's inspection effort (Cho et al 2019), the supplier's sustainability efforts (e.g., Kraft et al 2018), or the supplier's violations (e.g., Kim 2015, Plambeck andTaylor 2015). To the best of our knowledge, the only exception to this is Kalkanci and Plambeck (2017), who also investigated the buyer's revelation of her relationship with the supplier.…”
Section: Related Literaturementioning
confidence: 99%
“…Specifically, some are beginning to publish the identities of their suppliers, whereas in the past they were strategically secretive (Marshall et al 2016). Nike historically refused experiments, Kraft et al (2017) find value for a buying firm in giving consumers visibility regarding wages paid in its upstream supply chain. Caro et al (2017), Fang and Cho (2015) and Plambeck and Taylor (2016) consider the sharing of audit reports among buying firms with a common supplier, which influences auditing effort and supplier responsibility effort.…”
Section: Introductionmentioning
confidence: 99%